Effects of Lycopene Treatments on Development, Hatchability, and Heart Rate of Zebrafish Embryos under Heat Stress Exposure - Tuska, Habib Syaiful Arif; Salsabila, Odifiannisa Ayu; Lonameo, Bonick Kartini; Hardian, Andreas Bandang; Lesmana, M. Arfan; Yesica, Reza (Faculty of Veterinary Medicine Universitas Brawijaya, 2024)
Lycopene, a potent antioxidant predominantly found in red-hued fruits and vegetables such as tomatoes, has been incorporated into embryonic maturation media in vitro, demonstrating enhancements in embryo quality. Despite these advancements, the specific effects of lycopene on Zebrafish embryo quality remain unexplored. This study aims to investigate the impact of lycopene (0.65 ppm) on the development of Zebrafish embryos, focusing on hatchability (HA), and heart rate (HR) under conditions of heat stress (HS). Fertile Zebrafish embryos at the gastrula stage were induced HS (30oC; 1 hour). The embryos will be segregated into two groups: those exposed to HS and nonHS (28oC). Each group will receive one of three treatments (four replicates): control / without lycopene (P1), 2μL lycopene (P2), and 4μL lycopene (P3). Observations using an inverted microscope was done every three up to 48 hours post-fertilization (hpf), and subsequently every five hours up to 96 hpf. Quantitative data obtained for HA and HR were analyzed with SPSS, One-Way ANNOVA (p<0.05). The antioxidants contained in lycopene can influence the speed and success of Zebrafish embryo development and HA exposed to HS. In addition, the antioxidant in lycopene can also suppress the HR frequency of Zebrafish embryos exposed to HS. However, more studies about the optimum dose, purity, and stability of the lycopene extract should be done to make a definitive conclusion.